Bond strength between acrylic resin and maxillofacial silicone - Haddad, Marcela Filié [UNESP]; Goiato, Marcelo Coelho [UNESP]; dos Santos, Daniela Micheline [UNESP]; Crepaldi, Nádia de Marchi [UNESP]; Pesqueira, Aldiéris Alves [UNESP]; Bannwart, Lisiane Cristina [UNESP] (FapUNIFESP (SciELO), 2012)
The development of implant dentistry improved the possibilities of rehabilitation with maxillofacial prosthesis. However, clinically it is difficult to bond the silicone to the attachment system. Objectives: This study aimed to evaluate the effect of an adhesive system on the bond strength between acrylic resin and facial silicone. Material and Methods: A total of 120 samples were fabricated with auto-polymerized acrylic resin and MDX 4-4210 facial silicone. Both materials were bonded through mechanical retentions and/or application of primers (DC 1205 primer and Sofreliner primer S) and adhesive (Silastic Medical Adhesive Type A) or not (control group). Samples were divided into 12 groups according to the method used to attach the silicone to the acrylic resin. All samples were subjected to a T-peel test in a universal testing machine. Failures were classified as adhesive, cohesive or mixed. The data were evaluated by the analysis of variance (ANOVA) and the Tukey's HSD test (α=.05). Results: The highest bond strength values (5.95 N/mm; 3.07 N/mm; 4.75 N/mm) were recorded for the samples that received a Sofreliner primer application. These values were significantly higher when the samples had no scratches and did not receive the application of Silastic Medical Adhesive Type A. Conclusions: The most common type of failure was adhesive. The use of Sofreliner primer increased the bond strength between the auto-polymerized acrylic resin and the Silastic MDX 4-4210 facial silicone.
Keywords: Acrylic resins; Dental implantation; Polymethyl methacrylate; Silicone elastomers